Bakti Sosial Sinergisitas TNI, POLRI, PEMKOT, ORMAS dan Mahasiswa UCIC Dalam Rangka Sumpah Pemuda dan Pelaksanaan Kampus Merdeka - Amroni Amroni; Dewi Laily Purnamasari; Marsani Asfi; Sudadi Pranata; Kusnadi Kusnadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
The synergy between TNI, POLRI, ORMAS, PEMKOT and students is a form of solidarity between components of society during the current Covid-19 pandemic. This synergy in social service aims to help some people directly affected by the COVID-19 pandemic so that they have better endurance. This social service activity is also in commemoration of the 93rd youth oath day in 2021. From Catur University Insan Scholar this activity is represented by BKM as a student organization at the university level. This social service activity is carried out by helping to provide material assistance in the form of basic food packages. Food packages of 2000 packages. The result of this Social Service activity is the distribution of a number of material assistance so that it can increase people's resilience to get out of the economic pressure due to COVID-19.